Dual COX/LOX inhibition : screening and evaluation of the effect of pyroligneous acid fractions of palm kernel shell as an anti-inflammatory agents - Zainab Rabiu,; Rosnani Hasham,; Zainul Akmar Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Inflammation is treated using Steroidal (SAIDs) and Non-steroidal (NSAIDs) anti-inflammatory drugs. These synthetic drugs act by inhibiting the activity of inflammatory mediators (Prostaglandins and Leukotrienes) and are known to have various side effects. The use of natural products as alternatives is gaining prominence due to effective therapeutic function with reduced side effects. Palm kernel shell biomass can be thermo-chemically converted into Pyroligneous Acid (PA), which have been found to contain phenols that have antioxidant activities and potential anti-inflammatory effects. In this study, the PA is derived from slow pyrolysis of palm kernel shell by fractionation using column chromatography. The fractions are then screened for Total Phenolic content using Folin ciocalteau assay and free radical scavenging activity using FRAP and DPPH procedures. Anti-inflammatory activity of COX and LOX pathways with the screened fractions, is determined using the LOX-5 and COX-2 assay by ELISA method. The fractions were found to have phenolic and free radical scavenging activity with high percentage yield. The fractions were also found to have dual inhibition for COX and LOX enzymes with IC50 values ranging for COX enzymes IC50 (17.04% - 48.42%) and LOX with IC50 (5.23% -53.34%). The findings of the present study indicate the potential for use of various fractions of pyroligneous palm kernel shell as a viable source of anti-inflammatory agents.